Colostrum Yield and Colostrum Suckled by Neonatal Buffalo Calves (Indian Journal of Animal Production and Management, 2024)
The colostrum production by buffaloes during  12 h after post birth was measured in three intervals  within 2 h after birth, 2 to 6 h after birth, and 12 h  after birth, by weigh-suckle-weigh method and hand  milked colostrum measured in measuring cylinder.  Average colostrum suckled by neonatal calf of  having average body weight 27.93 kg in first feeding  at 2 h, 2nd feeding at 6 h and 3rd feeding at 12 h  after birth were 275.63 mL, 413.13 mL and  656.31mL respectively and average total colostrum  suckled by neonatal calves at 6 hours after birth  calving and total colostrums suckled in 12 h after  birth were 688.76 mL and 1345 mL respectively,  with a total yield of 4112 mL of colostrum (suckled  plus hand milked) equal to 14.72 % of body weight  of the calf. It was found that the total colostrums  yield at 6 h and 12 h of after birth (including hand  milked and colostrums suckled) were 2252.40 mL  and 1867.63 mL, respectively. It was recorded that,  average colostrums suckled (per cent of body  weight of calf) at 2 hours in first feeding, at 6 hours  in 2nd feeding and at12 hours in 3rd feeding of after  birth were 1.26, 1.47, and 2.46, respectively and  average total colostrums suckled (per cent of body  weight of calf) at 6 h after birth (including 1st feeding  and 2nd feeding) and at 12 h after birth (includes all  three feedings up to 12 h after birth) were, 2.34 and  6.68, respectively.
Keywords: buffalo; neonatal calves; colostrum yield; colostrum suckled